ANALISIS TANGGUNG JAWAB SHOPEE SEBAGAI PENYEDIA SISTEM ELEKTRONIK TERHADAP PENJUALAN LIPTINT VARIAN GLOSSY STAIN DARI EMINA YANG SAMA SECARA KESELURUHAN OLEH TOKO CANTIK. QUENBEE: Shopee's Responsibility for the Sale of Emina Liptint Glossy Stain Variant by Store Cantik.QueenbeeV - Fortuna, Natasya; Lestari, Suci (AMICUS CURIAE, 2024)
This research discusses the analysis of Shopee's liability in handling the sale of products that violate intellectual property rights, especially trademark rights. The problem in this article are whether the Emina Liptint Brand Emina Production is the same as a whole, sold by Cantik.Queenbee at Sshopee is a trademark infringement according to the Trademark Law? and how Shopee's legal liability as an electronic system provider against the sale of liptin glossy stain variants of the same Emina as a whole. The first conclusion is that there is a trademark infringement of Emina's glossy stain variant liptint products sold by Cantik.Queenbee at Shopee, which violates Article 100 paragraph (1) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Second, Shopee's liability as an electronic system provider is seen through EIT Law article 15, Government Regulation IEST article 5, Government Regulation TES article 22 paragraph (1), CL No. 5 of 2016. Cooperation is needed between the Ministry of Communication and the Directorate General of Intellectual Property to develop more effective regulations related to brand infringement in the marketplace.